Integrated eQTL mapping approach reveals genomic regions regulating candidate genes of the E8-r3 locus in soybean - Gélinas Bélanger, Jérôme; Copley, Tanya Rose; Hoyos-Villegas, Valerio; O’Donoughue, Louise (Frontiers in Plant Science, 2024)
Deciphering the gene regulatory networks of critical quantitative trait loci associated with early maturity provides critical information for breeders to unlock soybean's (Glycine max (L.) Merr.) northern potential and expand its cultivation range. The E8-r3 locus is a genomic region regulating the number of days to maturity under constant short-day photoperiodic conditions in two earlymaturing soybean populations (QS15524F2:F3 and QS15544RIL) belonging to maturity groups MG00 and MG000. In this study, we developed a combinatorial expression quantitative trait loci mapping approach using three algorithms (ICIM, IM, and GCIM) to identify the regions that regulate three candidate genes of the E8-r3 locus (Glyma.04G167900/GmLHCA4a, Glyma.04G166300/GmPRR1a, and Glyma.04G159300/GmMDE04). Using this approach, a total of 2,218 trans (2,061 genes) / 7 cis (7 genes) and 4,073 trans (2,842 genes) / 3,083 cis (2,418 genes) interactions were mapped in the QS15524F2:F3 and QS15544RIL populations, respectively.From these interactions, we successfully identified two hotspots (F2_GM15:49,385,092-